Dough Development, Texture and Organoleptic of Steamed Bread Addition with Moringa Leaf Flour - Firdausy, Haris Maulana; Widodo, Richardus; Panjaitan, Tiurma W Susanti (Universitas Dr Soetomo, 2020)
Steamed breads are economic hawker that can be enjoyed by all people. Steamed bread fortified with moringa leaves will make relatively low nutritional products raised in nutritional standards. It produces products that are not only filling but also steamed buns are also highly nutritious.Â Moringa leaves contain many nutrients and benefits, and their use has not been maximized. This study aims to determine the aspects of texture, dough development capacity, and the level of organoleptic acceptance of steamed bread with the addition of moringa leaf flour. Texture testing is done using a penetrometer and getting P1 to be the softest product compare to others mixtures (P0, P2, P3) with an average value of 223 mm/50g/10s. Measurements of the dough expandability show that P1 can expand by 53.8%. Furthermore, in terms of organoleptic, P1 treatment is preferred by most (60%) panellists for the colour category. The addition of moringa leaf flour by 5% (P1) and 10% (P2) is preferred by 40% and 45% for the aroma category. In contrast for taste, 40% of panellists favour steamed bread without the addition of moringa leaf flour (P0). Then, the more addition of Moringa leaf flour, the less number of panellists who like it.